Retention of bacteria in cellulose fibres as a means of reducing biofouling in paper pulp production processes - M. O. Pereira (1998)
The effectiveness of a non-oxidising biocide (a carbamate-based solution) as a retention agent for cells of Pseudomonas fluorescens in a paper pulp suspension was studied, as a way to reduce biofouling in pulp and paper production processes. The results indicated that the addition of the biocide not only changed the pH of the paper pulp suspension, but also shifted the surface charges of the bacterial cells from negative to neutral or positive values, depending on the pH value and the biocide concentration Therefore, since the paper pulp fibres are negatively charged, adhesion of bacterial cells to the fibres is promoted. Hence, it was possible to obtain an increase in cell retention on the cellulose fibres from 45% to 75%, within less than 5 min of contact between the carbamate and the pulp suspension. This effect increased with the concentration of carbamate solution in the fibre suspension (100-300 mgl-1), and was always higher than in the absence of biocide.